Managerialism and democratic governance in Portuguese higher education: Assessing the impact of the legal framework - Mineiro, J. (Higher Education Policy, 2025)
This paper explores the impact of managerialism on democracy in Higher Education by analyzing the implications of the Legal Framework of Higher Education Institutions in Portugal from 2007 to 2022. The findings, drawn from data on representation and electoral participation, reveal deficiencies in democratic governance. Notably, General Councils lacking legitimacy, and there is insufficient representation within the teaching and research community. Consequently, the disparities in electoral representation and labor rights disproportionately affect those facing precarity and job insecurity. The law's inability to strengthen accountability, transparency, and participation underscores the urgent need to promote democratic governance within public higher education institutions. By shedding light on the impacts of the Legal Framework, this research emphasizes the crucial task of evaluating and enhancing democratic governance in higher education for the benefit of the academic community and society at large.